Upaya Pemberantasan Penularan Penyakit TB Paru dan Manajemen Dahak Menuju Eliminasi TB 2030 - Pius A. L. Berek; Maria Fatimah W. A. Fouk; Yovita Made; Francisca Amaral (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Pulmonary tuberculosis (TB) is one of the infectious diseases that is of global concern. This disease is caused by the bacteria Mycobacterium tuberculosis which attacks the lungs and can spread through the air when the sufferer coughs or sneezes. The method of community service activities in the form of education is an effort to provide an understanding of tuberculosis and its treatment, as well as good and correct phlegm management. The service results showed an increase in community knowledge regarding TB, including symptoms, how it was transmitted, preventive measures, and good and correct cough management. There was an increase in community knowledge where the pre-test results of 57.14 increased to 90.77 in the post-test. Collaboration between academics, village governments, NGOs, and community leaders as well as posbindu cadres is the key to the success of the government's program to eliminate TB in 2030. It was concluded that through ongoing efforts and adaptation to local needs, knowledge about TB and phlegm management can help reduce the transmission of this disease significantly and support government efforts to eliminate TB 2030 both at the Kabuna Village level, Belu Regency, and even Indonesia as a whole.